Protective effects of oxymatrine against DSS-induced acute intestinal inflammation in mice via blocking the RhoA/ROCK signaling pathway. Issue 7 (19th July 2019) - Wang, Yifan; Shou, Zhexing; Fan, Heng; Xu, Meng; Chen, Qianyun; Tang, Qing; Liu, Xingxing; Wu, Hui; Zhang, Man; Yu, Ting; Deng, Shuangjiao; Liu, Yujin
Abstract : Oxymatrine (OMT) is an important quinoxaline alkaloid that has a wide range of pharmacological effects and has been shown to alleviate ulcerative colitis due to its profound anti-inflammatory effects. The RhoA/ROCK (Rho kinase) signaling pathway has been shown to be related to the pathogenesis of several autoimmune diseases; however, the specific mechanisms of RhoA/ROCK signaling in inflammatory bowel disease (IBD) remain elusive. Therefore, we sought to determine whether OMT could ameliorate acute intestinal inflammation by targeting the RhoA/ROCK signaling pathway. The potential therapeutic effect of OMT on acute intestinal inflammation and its impact on the RhoA/ROCK signaling pathway were assessed in six groups of mice treated with low, medium and high doses of OMT (25, 50 and 100 mg/kg, respectively), and an inhibitor of ROCK, Y-27632, as a positive control, after initiating dextran sodium sulfate (DSS)-induced acute intestinal inflammation. The model group and normal group were injected intraperitoneally with equal doses of PBS. Our results showed that OMT treatment could protect the integrity of the epithelial barrier, relieve oxidative stress, inhibit the expression of inflammatory mediators and pro-inflammatory cytokines, restrain the differentiation of Th17 cells and promote the differentiation of Treg cells via inhibition of the RhoA/ROCK pathway, thus providing therapeutic benefits for ulcerative colitis (UC). Therefore, inhibiting the RhoA/ROCK pathway might be a new approach that can be used in UC therapy, which deserves to be investigated further.